Low peripheral oxygen saturation as a risk factor for brain abscess in children with cyanotic congenital heart disease - Nadia Qoriah Firdausy; Indah Kartika Murni; Agung Triono; Noormanto Noormanto; Sasmito Nugroho (Indonesian Pediatric Society, 2018)
Background Brain abscess is a severe infection of brain parenchyma, which occurs in 25-46% of cases of uncorrected cyanotic congenital heart disease. Low arterial oxygen saturation is the main risk factor for brain abscess in children with cyanotic congenital heart disease, however, the arterial oxygen saturation test is invasive and not routinely done in our setting. Objective To evaluate low peripheral oxygen saturation as a risk factor for brain abscess in children with cyanotic congenital heart disease. Methods We conducted a matched, case-control study at Sardjito Hospital, Yogyakarta for children aged less than 18 years with cyanotic congenital heart disease, from 2010-2016. Case subjects were children with brain abscess complications. The control group had only cyanotic congenital heart disease, and were matched for age and sex to the case group. During hospitalization due to the brain abscess complication in the case group, data regarding peripheral oxygen saturation, polycythemia, pneumonia, sepsis, dental caries and restricted pulmonary blood flow were collected and compared between both groups. Results During the study period, 18 children with cyanotic congenital heart disease had brain abscesses. This group was compared to the control group of 36 children. Bivariate analysis revealed that the lowest level of peripheral oxygen saturation (OR 0.92; 95%CI 0.85 to 0.98; P=0.02) and dental caries (OR 3.3; 95%CI 1.01 to 11.18; P=0.04) were significant risk factors for brain abscess. However, in the multivariate analysis, the only statistically significant risk factor associated with brain abscess was the lowest level of peripheral oxygen saturation (OR 0.92; 95%CI 0.86 to 0.99; P=0.04). Conclusion Low peripheral oxygen saturation is a significant risk factor for brain abscess development in children with cyanotic congenital heart disease. A decrease of 1% peripheral oxygen saturation may increase the risk of brain abscess by 8%.